Political culture of pupils in the modern russian society - A V Ivashchenko; I A Tyutkova (Peoples' Friendship University of Russia (RUDN University), 2009)
The article concerns conceptual bases of students' political culture which reflect its essence, functions and peculiarities of the formation process.